ANALISIS DAMPAK LIMBAH DOMESTIK RUMAH TANGGA TERHADAP PENCEMARAN LINGKUNGAN DI TANJUNGBALAI SUMATERA UTARA - Rehuliana Ninta Br Sitepu (CV. Adiba Aisha Amira, 2024)
Domestic waste is waste from bathrooms, kitchens, used domestic industrial waste, and human waste which, if not handled, can pollute and poison the environment due to domestic activities. The impact of domestic waste is a serious problem for all of us, because most ordinary people do not know the impact of littering. There are many ways to deal with waste such as sorting, recycling, composting, etc.